The Decline of Islam and the Progress of the Western World - Saputra, Junifer; Erman, Erman; Hasnah, Radhiatul (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article aims to find out the history of the decline of Islam and the progress of the Western World. This research uses library research or literature study; the research source focuses on books and articles related to the discussion. The result of this research is to find out that the decline of Islam occurred during the Abbasid dynasty, when there were various problems that caused Islamic civilization to begin to weaken and even decline. The decline of Islam was primarily caused by the Mongol invasion, which marked the Abbasid period's collapse. In addition, fragmentation and intellectual stagnation were also major factors in the collapse of Islam in the Abbasid period. While the progress of the Western World is inseparable from the history of Islamic civilization, which experienced progress and decline, the factors that became the main cause in the progress of the Western World are Renaissance and Humanism, which marked the beginning of the progress of the western world with the transition of social changes in society to massive. The Science Revolution, Industrial Revolution, Colonialism, and Imprealism are also important factors in the progress of the Western World.